2021
DOI: 10.1038/s41598-021-01970-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and outcomes of 23 patients with secretory carcinoma of major salivary glands

Abstract: This retrospective study investigated the clinicopathological characteristics of secretory carcinoma of salivary glands (SCSG) in 23 patients with histopathologically confirmed SCSG between January 2010 and December 2020. In total, 13 males and 10 females (ratio, 1.3:1) aged 10 − 69 years (median, 45 years) were enrolled in this study; the average disease duration was 2.44 years (0.25–20 years). Twenty-one patients (91.3%) had SCSG in the parotid gland, and two (8.7%) in the submandibular gland. All patients h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 42 publications
(46 reference statements)
1
24
0
Order By: Relevance
“…The success of NTRK-targeted therapies in patients with secretory carcinoma harbouring NTRK gene fusions represents a significant step forward for genetic based approaches in SGC. These patients were not represented in our cohort, possibly due to the lower frequency of recurrence in this subtype in comparison to other salivary gland cancer types [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The success of NTRK-targeted therapies in patients with secretory carcinoma harbouring NTRK gene fusions represents a significant step forward for genetic based approaches in SGC. These patients were not represented in our cohort, possibly due to the lower frequency of recurrence in this subtype in comparison to other salivary gland cancer types [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this phase, 2 case reports 23,24 were excluded and finally, 13 articles were included for quantitative synthesis (Figure 1). 7,8,[12][13][14][15][16][17][18][19][20][21][22] 3.1 | Methodological characteristics of the studies Data extracted from all 13 studies including details on the country of origin, authors, total number, and histopathological type of SGTs and pattern of pan-TRK IHC manifestation are provided in Tables S1 & 1.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were conducted between 2017 and 2022, in more than 5 different countries: 4 in the USA, 7,12-14 2 in France, 16,18 3 in Japan, 8,15,21 2 in China 19,20 1 in Taiwan, 22 and 1 was multicentric. 17 A total of 623 different SGTs including 255 SCs and 82 AciCCs were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, due to the small cohorts included in previous studies, the risk of nodal metastasis, local recurrence, distant metastasis, and disease-related death ranged widely. The reported frequency of nodal metastasis ranged from 3% to 43%, 1,[15][16][17][18][19] local recurrence ranged from 3% to 38%, 1,15-20 distant metastasis ranged from 0% to 17%, 1,15,16,18,19,[21][22][23] and disease-related mortality ranged from 0% to 33%. 1,4,[16][17][18][19][20]22,24 Although these data indicated that SC generally behaves as a lowgrade salivary gland carcinoma, nodal metastasis, recurrence, and distant metastasis may occur in a small subset of cases.…”
Section: Discussionmentioning
confidence: 99%